THE INFLUENCE OF GADGET PLAYING ON ADOLESCENT BEHAVIOR IN FAMILIES IN PEMATANG KUALA VILLAGE - Mutia Febriyana (Proceeding International Seminar of Islamic Studies, 2023)
The world has entered a new era, namely the era of technology and communication. The development of technology and communication is happening very rapidly, technology continues to create various types of gadgets that are classified as high-technology gadgets. In general, technology (gadgets) has become an inseparable part of a person's life. Efforts are needed to increase awareness, knowledge, and skills so that they can continue to use the internet through their gadgets intelligently. However, nowadays gadgets in their use are often excessive and affect various aspects of life. This influence can be felt both by the self and by the people around the user. One of the closest environments affected by the use of gadgets is the family. This study aims to find out how the influence of gadgets on the behavior of adolescents in the family. The research is based on changes in adolescent behavior due to excessive use of gadgets. This research uses a qualitative approach with descriptive methods. Data was obtained through a questionnaire that used gadgets excessively in Pematang Kuala Village. Data analysis was carried out from the beginning of the study to reporting. The results showed that teenagers in Pematang Kuala Village used gadgets for 5-7 hours (300-420 minutes) a day, which meant that these teenagers were already addicted to gadgets. The excessive use of gadgets hurts the behavior of adolescents in the family, including emotional instability which causes adolescents to become irritable, emotional, anxious, and even withdrawn.